Single mothers' income in twelve rich nations: Differences in disadvantage across the distribution - Susan Harkness (Luxembourg Income Study (LIS), 2022)
Previous research has shown single mothers to be less well-off and at higher risk of poverty than mothers in couples. In this article, I extend current research by examining how single motherhood affects income at different quantiles of the distribution in twelve rich nations. Using harmonised data from the Luxembourg Income Study (LIS), I first show how the distribution of single mothers' income differs to that of couples with children. Using unconditional quantile treatment effect (QTE) models, I then assess the influence of single motherhood on income at different points of the distribution. I find that, in all countries, single motherhood is associated with large reductions in income across the distribution and that these gaps cannot be explained by differences in single and partnered mothers' individual and family characteristics or employment. I also find striking variations across countries in the effect of single motherhood on income at different points of the distribution. In some countries, such as the United Kingdom, single motherhood has a greater effect on income at the top of the income distribution than the bottom. In other countries, such as the United States, the reverse is true with the effect on income being largest at the bottom of the distribution. I conclude by discussing the role that employment and social policies may play in driving cross-country differences in the income gradient associated with single motherhood across the distribution.
Keywords: 330; single mothers; inequality; quantile treatment effects; tax and benefits; employment